Podstawowe typy strukturalne nazw własnych współczesnych teatrów w Polsce - Kowalik , Krystyna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2010)
The subject of the article are the names of currently open Polish theatres. Attention is focused on the formal structure of the names, i.e. the number and type of the components of the official name of a theatre. Theatre names are nominal in nature and are saturated with vocabulary from the broad semantic field of theatre. The constitutive element of most names is the lexeme THEATRE. Additional identifying and defining elements are adjectives and common or proper (name of the patron) nouns. The minimal name consists of two elements. Other names vary as for their length, yet the order of elements extending the name can be easily established.